Impact of Quality Housekeeping Services Towards Guest Satisfaction in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
AbstractHousekeeping plays an important role in any hospitality setting. This department is taskedwith maintaining the hotel's cleanliness and keeping the hotel in a desirable ambiance. Thisstudy determines the overall vitality of the research idea that was originally proposed by thebachelor of science in hospitality management students of Bestlink College of the Philippines.It Emphasizes the capability of the proposed recommendation for the satisfaction of theguests concerning the quality of housekeeping services in McHotel Novaliches, involving theplanning to enhance, implement, and change the negative perception of many guests aboutservices in the said hotel. In order for the guests to unwind and enjoy their stay when they aretraveling far from home, the housekeepers should keep each guest's room tidy and organized.The enthusiasm, passion, and commitment of its housekeeping staff are said to be among themotivating aspects for providing high-quality service. By delivering quality service, thedepartment can contribute to establishing and preserving the hotel's favorable reputation andimage.The result shows that guests are satisfied with the quality of housekeeping services in terms ofreliability, responsiveness, empathy, assurance, and tangibility. On the other hand, guests orrespondents are also satisfied with how the hotel maintained guest loyalty in terms oftechnology, rooms, amenities, and services.Hotels should always be willing to be involved with trends in terms of providing quality servicesin order to satisfy guests, and they should constantly strive to improve their services based onguests' feedback. In order to maintain guest satisfaction, they should measure it regularly andimplement programs that offer rewards to loyal guests. Rewarding guests through the createdprograms is like letting them enhance their experience. They should also invest more intechnology because it has a vital contribution to improving guest satisfaction. In order to haveeasy access, the hotel should upgrade its facilities and include certain modern equipment, andit should improve its front area to attract potential guests.
Keywords: Hospitality Management